High School students' perception of the use of Medicinal Plants: a teaching tool in the disciplines of Biology and Chemistry in Quirinópolis, Góias, Brazil (Research, Society and Development, 2021)
The disciplines of Biology and Chemistry can be used as tools for the dissemination and expansion of ethnobotanical knowledge regarding the use of medicinal plants. The awakening of this knowledge in students contributes to the improvement of interest in experimental sciences and, consequently, provides a feeling of belonging to nature on the part of those involved. In this context, this research aimed to evaluate the perception of high school students about the use of medicinal plants in Quirinópolis, Goiás. The research was conducted with the application of questionnaire 1, followed by a practical class using the tincture method in the preparation of the medicine with medicinal plants, and, ending with the application of questionnaire 2. For the practical class, the students collected the plants and brought them to the Chemistry/Biology Laboratory. Most students said they use plants for medicinal purposes with guidance from family members. Twelve plant species were mentioned, the majority exotic, acquired for the most part from their own cultivation, and the most mentioned were Plectranthus barbatus Andrews, Chenopodium ambrosioides L., Matricaria chamomilla L. and Bidens pilosa L. The most used part was the leaves, the predominant form of preparation was infusion and the main use was for the treatment of flu. The practical class was considered by the students as an innovative experience with fruitful scientific knowledge. Most of them believe that knowledge about medicinal plants can contribute to the learning of Chemistry and Biology and the experience arouses interest in practical applications of scientific concepts addressed in the classroom.